2004
DOI: 10.1002/ss.118
|View full text |Cite
|
Sign up to set email alerts
|

Support programs that work

Abstract: Research shows that Latino students are grossly underrepresented in higher education. In this chapter, however, we show how family, community, and institutional partnerships can be an evidence‐based practice for faculty and student affairs professionals who wish to increase Latino participation and graduation rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Nearly all (86%) of Latinos report feeling that one cannot be too careful about whom one places trust in, while 61% of the general public reported feeling the same (Taylor et al, 2012). e importance of relationships for Latino college students means that cultivation of social capital, particularly with institutional personnel, is key to enhancing their success (Brown, 2008;Mina, Cabrales, Júarez, & Rodríguez-Vásquez, 2004). Access to social capital through social networks that provide encouragement, support, and useful information can help Hispanic students succeed (e.g., Núñez, 2005;Saunders & Serna, 2004;Ríos-Aguilar & Deil-Amen, 2012;R.…”
Section: Social Capitalmentioning
confidence: 99%
“…Nearly all (86%) of Latinos report feeling that one cannot be too careful about whom one places trust in, while 61% of the general public reported feeling the same (Taylor et al, 2012). e importance of relationships for Latino college students means that cultivation of social capital, particularly with institutional personnel, is key to enhancing their success (Brown, 2008;Mina, Cabrales, Júarez, & Rodríguez-Vásquez, 2004). Access to social capital through social networks that provide encouragement, support, and useful information can help Hispanic students succeed (e.g., Núñez, 2005;Saunders & Serna, 2004;Ríos-Aguilar & Deil-Amen, 2012;R.…”
Section: Social Capitalmentioning
confidence: 99%
“…Feeling a sense of belonging enhances engagement, involvement, and participation within these organizations which then translates to enhancing the sense of belonging to the larger campus. Belonging facilitates a host of additional educational outcomes as previous studies have demonstrated including completion (Garcia, 2005; Hernandez, 2002; Hurtado et al, 2007; Mayo et al, 1995; Mina et al, 2004; Suarez et al, 1997).…”
Section: Discussionmentioning
confidence: 94%
“…As a result, the literature specifically centering the experiences of Latin@ Greeks is very limited. In fact, only a handful of sources (Estrada, Mejia, & Hufana, 2016; Fajardo, 2015; Garcia, 2005; Mina, Cabrales, Juarez, & Rodriguez-Vasquez, 2004; Olivas, 1996; Orozco, 2003; Orta, Murguia, & Cruz, 2017) discuss the topic. This dearth of information on the unique experiences of minority Greeks provides both a limited empirical context for this work, as well as provides a rationale for researching this understudied student population.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Entering a new and unfamiliar world, students may experience an "outsider within" status, enduring a great deal of social isolation (Oliver, Rodriquez, & Michelson, 1985); intimidation; and a sense of being pulled between two different worlds, their campus and cultural communities (Gloria & Pope-Davis, 1997;Mina et al, 2004). For students from cultural backgrounds that place high value on the family, family obligations such as housework or child care may become major sources of stress in conjunction with academic and other personal responsibilities (Constantine & Chen, 1997;Lopez, 1995).…”
mentioning
confidence: 99%